2021
DOI: 10.1016/j.bios.2020.112868
|View full text |Cite
|
Sign up to set email alerts
|

Development of a SARS-CoV-2-specific biosensor for antigen detection using scFv-Fc fusion proteins

Abstract: Coronavirus disease 2019 (COVID-19) is a newly emerged human infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In a global pandemic, development of a cheap, rapid, accurate, and easy-to-use diagnostic test is necessary if we are to mount an immediate response to this emerging threat. Here, we report the development of a specific lateral flow immunoassay (LFIA)-based biosensor for COVID-19. We used phage display technology to generate four SARS-CoV-2 nucleocapsid protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 17 publications
1
85
0
1
Order By: Relevance
“…A research work focused on LFIA-based biosensor for COVID-19 detection was conducted by Kim et al [ 83 ]. They utilized phage technology to produce four SARS-CoV-2 nucleocapsid protein (NP)-specific single-chain variable fragment-crystallizable fragment (scFv-Fc) fusion antibodies.…”
Section: Sars-cov-2 Detection Based On Applied Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A research work focused on LFIA-based biosensor for COVID-19 detection was conducted by Kim et al [ 83 ]. They utilized phage technology to produce four SARS-CoV-2 nucleocapsid protein (NP)-specific single-chain variable fragment-crystallizable fragment (scFv-Fc) fusion antibodies.…”
Section: Sars-cov-2 Detection Based On Applied Analytical Methodsmentioning
confidence: 99%
“…In addition, the results indicated that the LFIA biosensor could successfully distinguish between SARS-CoV-2 positive and negative samples. The detection limit of LFIA biosensor would meet the conditions for the clinical use through optimization [ 83 ]. The effect of applying nanoparticles on sensitivity and selectivity of LFIA detection is investigated by Huang et al [ 26 ].…”
Section: Sars-cov-2 Detection Based On Applied Analytical Methodsmentioning
confidence: 99%
“…Phage display-derived antibodies are among the multiple approaches quickly deployed to generate monoclonal antibodies directed to SARS-CoV-2 ( Jiang et al., 2020 ). In this emergence scenario, anti-nucleocapsid protein antibodies have been generated through phage display for diagnostic purposes ( Kim et al., 2021 ). However, the most efforts have been focused on spike protein, and specifically to the receptor binding domain (RBD), to directly block the interaction with the host receptor, aiming to select neutralizing antibodies for novel therapeutics development.…”
Section: Recombinant Antibodies Against Virusesmentioning
confidence: 99%
“…ScFv-Fc antibodies are specific to SARS-CoV-2-NP antigen with high affinity, and three specific antibody pairs are used on the cellulose nanosphere (CNB)-based LFIA kit. The detection limits for the best pair are found as 2 ng of antigen protein and 2.5 x 104 pfu of the cultured virus ( 66 ).…”
Section: Nanoparticle-based Detection Strategies Of Covid-19mentioning
confidence: 99%